Korupsi Demokratis dalam Partai Politik:Studi Kasus Penyelenggaraan Pemilukada Lampung - Irham, Muhammad Aqil (UI Scholars Hub, 2016)
After 1998 Reformation, Indonesia has been experiencing democratization and decentralization. Among others, general election for local government (pemilukada) since 2005 is an implementation of democratization and decentralization. Although democratization in Indonesia was praised by some researchers, many others also figured out some corruptive actions in the democratic process. Warren’s conception about democratic corruption helped us to understand the paradox of post-Reformation democratization and decentralization. According to Warren, corruption in a democracy is a duplicitous exclusion that gives an advantage to few parties in the expense of the others who are excluded from the process of decision-making and collective action. However, the author suggests that there is incompleteness in Warren’s conceptualization when he identified the location of corruption that is differentiated in a democratic regime. Warren identified only four locations of corruption, that is the state, public sphere, civil society, and market. Took local elections in Lampung as a case study, this article identified other location, that is the political party. This article argues, corruption of democracy in the political party is indicated primarily by political party’s centralism in recruiting and selecting local leader candidates.